Transient remodeling of gut metabolism supports juvenile growth and adult fitness in Drosophila. - Lefranc, C.; Fichant, A.; Storelli, G. (Nature communications, 2026)
Animals develop through discrete life stages with specific goals, such as growth or reproduction. Achieving these goals may require temporary changes in the function of certain organs, but these adaptations remain poorly understood. In Drosophila, the juvenile phase is characterized by a several-hundred-fold increase in body mass, which culminates in a rapid growth spurt before puberty. Here, we show that this growth spurt is supported by acute remodeling of gut metabolism. Midway through the juvenile phase, steroid hormone and hepatocyte nuclear factor 4 induce digestive function, lipid metabolism and nutrient export in the intestine, thereby accelerating growth and maturation. Gut metabolic remodeling ceases at puberty but has a lasting impact on physiology, enhancing adult reproductive fitness and resilience to environmental stress. Our work identifies an endocrine-metabolic axis that synchronizes gut function with developmental demands, and provides insights into how systemic signals dynamically remodel organ metabolism to optimize life history strategies.